PENGARUH PERAN KEPEMIMPINAN, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA UPTD PUSKESMAS KECAMATAN KLARI KABUPATEN KARAWANG - Sukmayanti, Eneng (Jurnal Manajemen dan Bisnis Kreatif, 2018)
ABSTRAK The purpose of this study is to obtain empirical evidence and to find clarity of phenomena and conclusions about the influence of leadership role, communication, and work environment on employee performance at UPTD Puskesmas Kecamatan Klari Kabupaten Karawang. This thesis is expected to contribute to the development of management science, especially as a contribution of scientific literature in human resources management, as reference material in scientific writing, as an information material, both for leaders and colleagues in District Health Office Karawang in the implementation of performance-based management, As a material consideration and input in making decisions and determine the direction of policy. The research is done by using quantitative method with descriptive and verification method, that is collecting, presenting, analyzing and doing hypothesis testing, and making conclusion and suggestion. Based on the results of the research analysis, the following conclusions are obtained: 1. The correlation of leadership (X1) with communication (X2) has a correlation coefficient value (r) of 0.512 and if interpreted by the closeness of relationship between these two variables has a fairly strong level of relationship (Sugiyono, 2005:255) and unidirectional because the value is positive. This shows that if leadership increases then communication will also increase. Conversely, if communication increases then leadership will also increase. 2. Communication correlation (X2) with work environment (X3) has correlation coefficient (r) value of 0.343 and if interpreted with the closeness of relationship of these two variables have a low level of relationship (Sugiyono, 2005:255) and unidirectional because the value is positive. This shows that if communication increases then the work environment will also increase. Conversely, if the work environment increases then communication will also increase. 3. The correlation of leadership (X1) with work environment (X3) has a correlation coefficient value (r) of 0.359 and if interpreted by the closeness of the relationship of these two variables have a low level of relationship (Sugiyono, 2005:255) and unidirectional because the value is positive. This shows that if leadership increases then the work environment will also increase. Conversely, if the work environment increases then leadership will also increase. 4. The magnitude of the influence of leadership role on employee performance is 24.4%. Based on the findings of this study can be concluded that the hypothesis of research that states "leadership has significant effect on employee performance" is acceptable. 5. The magnitude of communication effect on employee performance is 14.2%. Based on the findings of this study can be concluded that the hypothesis of research that states "communication has significant effect on employee performance" is acceptable. 6. The amount of work environment influence on employee performance is 13.4%. Based on the findings of this study it can be concluded that the research hypothesis which states "work environment contribute significantly to the performance of employees" is acceptable. 7. Simultaneously leadership (X1), communications (X2), and work environment (X3) have a significant effect on employee performance (Y) of 52.0%. The remaining 48.0% is the effect that comes from other factors. Keywords : Role of Leadership, Communication, Work Environment, Employee Performance